Determination and Removing of Lead and Nickel in Water Samples by Solid Phase Extraction Using a Novel Remazol Black B-Sulfonamide Polymeric Resin - Timur, Irfan; Senkal, B. Filiz; Karaaslan, Nagihan M.; Bal, Tulin; Cengiz, Emine; Yaman, Mehmet (Bentham Science Publ Ltd, 2011)
In this study, Remazol Black B-containing sulfonamide resin was synthesized, characterized and used as a new sorption material in solid phase extraction for the determination of lead and nickel in water samples. The optimization of the parameters including pH, preconcentration period and the volumes of initial and elution solutions was performed. The optimum pH, preconcentration period and eluate volume were found to be 2.8, 30 min and 3.0 mL, respectively. In the measurement step, atomic absorption spectrometry was used. An enhancement of 350-fold in the sensitivity of Pb was achieved by combination of the slotted tube atom trap-atomic absorption spectrometry together with the optimized preconcentration method. The limits of detection were found to be 0.15 ng mL(-1) for Pb and 0.75 ng mL(-1) for Ni. The Pb and Ni concentrations in the natural water samples were found to be in the ranges of 0.9-8.0 ng mL(-1) and < 3.0-50.0 ng mL(-1), respectively. It was concluded that the developed procedure can be used as removing method because the high adsorption capacity was obtained by the optimized conditions.
Keywords: Lead and nickel removing; Preconcentration; Remazol black B-containing sulfonamide resin; Water